Penetrating cardiac injury resulting in a bullet embolus: a case report - Sammy Shihadeh; Anwar Khan; Kristen Walker; Ali Al-Rawi; Alfredo Cordova (Journal of Trauma and Injury)
Bullet embolism is a potential complication of a gunshot wound, especially with a low-velocity missile. This is because the trajectory of the low-velocity bullet can be significantly slowed as it passes through tissue. An unusual form of travel can occur in which the bullet enters the vasculature but does not have enough kinetic energy to create a through-and-through wound, leading it to remain inside the vasculature. Once inside the vasculature, the bullet could migrate to different parts of the body, potentially causing complications such as ischemia, becoming a source of thromboembolism, or functioning as a nidus for infection. The management of a bullet embolism varies from case to case, as each patient with this issue has a unique body habitus that can result in infinite possibilities of the trajectory and destination of the bullet embolus. Additional damage to surrounding vasculature or tissue can occur, as well as embolization of the bullet to critical areas of the body. Here we present the case of a 72-year-old man who had a self-inflicted gunshot wound to the chest with a low-velocity bullet, which penetrated the right atrium of the heart. It traveled into the venous vasculature through the right atrium, into the inferior vena cava, and eventually settled in the right internal iliac vein. He refused further intervention and management after initial workup and resuscitation.